Analysis of Errors in the Use of the ‘Adad Ma’dud of the Third Reguler of the Subject of Arabic Language Lessons in the Boarding School of Tarbiyatul Mu’allimin al-Islamiyah Prenduan Sumenep Madura - Bidari, Bidari; Jamilah, Wafiqatul (Universitas Al-Amien Prenduan, 2023)
Third regular students made various forms of Arabic conversation and writing errors when using numbers (â€˜adad maâ€™dud). There are as many errors as when using â€˜adad maâ€™dud. Given this situation, few learners make various mistakes when using â€˜adad maâ€™dud for daily conversations or writing. The purpose of this study is to understand the forms and causes of errors, as well as how to solve the problem of students using quantity and counting in Third regular students in the boarding school of tarbiyatul muâ€™allimin al-islamiyah prenduan. Researchers used qualitative methods and descriptive types to collect data in a triangular manner through observation, interviews, and testing, in order to identify errors made by Third regular students in the boarding school of tarbiyatul muâ€™allimin al-islamiyah prenduan when using â€˜adad maâ€™dud. The theme of this study is Third regular students in the boarding school of tarbiyatul muâ€™allimin al-islamiyah prenduan. The last thing about writing this study is that Third regular students made mistakes when using â€˜adad maâ€™dud, and they were unable to distinguish how to use singular and additive numbers, positive numbers, ordinal numbers, and mentioned numbers, Number of women. The reason is that girls lack understanding of quantity, quantity, and its rules, schools lack interest in cultivating girls, students use incorrect learning methods, students have difficulty learning Arabic, and their practice of using Arabic is reduced. The decrease in the number, quantity, and interest of students in using teaching aids in the classroom teaching process, as well as the decrease in students' enthusiasm during the classroom teaching process. The solution is to develop teaching methods, increase the time allocation of learning materials, and develop teaching methods.Â